2021
DOI: 10.7759/cureus.16202
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Marijuana Consumption Leading to High-Grade Atrioventricular Block in a Young Male

Abstract: Cannabis usage is increasing throughout the world for both medicinal and recreational purposes. Several countries and states have legalized cannabis, and physicians can expect to encounter more patients who use or abuse cannabis. Adverse cardiovascular effects of cannabis like myocardial infarction, cardiomyopathy, and arrhythmias have been well described but bradyarrhythmia is rare and the mechanisms are not well pronounced. A 26-year-old male with a history of chronic cannabis smoking presented with complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Studies have documented toxicological effects in different models exposed to cannabis ingredients [ 12 , 13 , 14 , 15 , 16 ]. A recent study reported that high-grade atrioventricular block was developed in a young male following chronic exposure to marijuana [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented toxicological effects in different models exposed to cannabis ingredients [ 12 , 13 , 14 , 15 , 16 ]. A recent study reported that high-grade atrioventricular block was developed in a young male following chronic exposure to marijuana [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented toxicological effects in different models exposed to cannabis ingredients [ 12 , 13 , 14 , 15 , 16 ]. A recent study reported that high-grade atrioventricular block was developed in a young male following chronic exposure to marijuana [ 14 ]. Moreover, a recent case series study concluded that vaping cannabis oil was associated with acute respiratory depression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dėl adrenerginės stimuliacijos sutrumpėja kardiomiocitų veikimo potencialo trukmė bei pakinta miokardo elektrofiziologinės savybės, sudarančios palankias sąlygas padidėjusio automatizmo bei micro-reentry aritmijų patogenezei, ypač jei asmuo turi polinkį į tachiaritmijas [1, 27,28]. Didesnės kanapių dozės stimuliuoja parasimpatinę ANS, ilgėja veikimo potencialo ir prieširdžių refrakterinis periodas, galimos macro-reentry aritmijos, įvairios bradiaritmijos, silpno sinusinio mazgo sindromas (SSMS), pauzės su sinkopėmis, AV blokados [1, 15,[29][30][31][32]. Aritmijų patogenezėje svarbi ir kanapių vartojimo sąlygota miokardo išemija, padidėjęs deguonies poreikis, trombocitų aktyvacija [1,20,[33][34][35].…”
Section: šIrdies Aritmijos Ir Kanapių Vartojimasunclassified
“…KVS pacientų su aritmija grupėje 7,8% patyrė PP, 7,5% SkT, 4,4% SVT 4,4%, 3,7% SkV 3,7%, 2,5% SSMS, 1,6 % trečio laipsnio AV mazgo blokadą [13]. Aritmijos kanapių vartotojams gali pasireikšti sinkopėmis, širdies plakimu, sąmonės sutrikimu, krūtinės skausmu, bendru silpnumu [15,25,[29][30][31][32][34][35][36]. Aprašyti su kanapių ar kanabinoidų vartojimu susijusių aritmijų atvejai, kai išsivystė gyvybei pavojingos skilvelinės aritmijos, kardiogeninis šokas, staigi mirtis arba laidumo sutrikimai, kai buvo reikalinga širdies stimuliatoriaus implantacija [6,15,25,30,32].…”
Section: šIrdies Aritmijos Ir Kanapių Vartojimasunclassified
“…Además, el uso crónico de THC se ha asociado con una mayor frecuencia de angina, probablemente debido a una disminución en el umbral anginoso, disminución de la transducción de señales del sistema nervioso simpático y parasimpático, aumento de la aldosterona sérica, vasoconstricción central y periférica e hipertensión (HTN). (Malviya et al, 2021;Subramaniam et al, n.d.;Yeniocak et al, 2021) METODOLOGÍA Se realizó una investigación con enfoque cuantitativo no experimental de tipo descriptivo y retrospectivo, mediante una búsqueda exhaustiva en diferentes bases de datos que incluyen: Google Scholar, PubMed, Embase y Elsevier en la literatura de habla inglesa, y Latindex, Scielo, y Google Scholar en la literatura de habla española. Se utilizaron como términos y/o palabras claves de búsqueda: efectos cardiovasculares del consumo de marihuana, patologías asociadas con el consumo de marihuana, marihuana e infarto de miocardio, marihuana e hipertensión.…”
unclassified